Moho Depth of Northern Baja California, Mexico, From Teleseismic Receiver Functions. Issue 6 (4th June 2021) - Ramírez, E. E.; Bataille, Klaus; Vidal‐Villegas, J. A.; Stock, J. M.; Ramírez‐Hernández, J.
Abstract: We estimated Moho depths from data recorded by permanent and temporary broadband seismic stations deployed in northern Baja California, Mexico, using the receiver function technique. This region is composed of two subregions of contrasting geological and topographical characteristics: the Peninsular Ranges of Baja California (PRBC), a batholith with high elevations (up to 2, 600 m); and the Mexicali Valley (MV) region, a sedimentary environment close to sea level. Crustal thickness derived from the P ‐to‐ S converted phases at 29 seismic stations were analyzed in three profiles: Two that cross the two subregions, in ∼W‐E direction, and the third one that runs over the PRBC in a N‐S direction. For the PRBC, Moho depths vary from 35 to 45 km, from 33°N to 32°N; and from 30 to 46 km depth from 32°N to 30.5°N. From a profile that crosses the subregions in the W‐E direction; Moho depths vary from 45 to ∼34 km under western and eastern PRBC, respectively; with an abrupt change of depth under the Main Gulf Escarpment (30°), from ∼32 to 30 km; and depths of 17–20 km under the MV. Moho depths of the profile in an ∼ W‐E direction at ∼31.5°N are from ∼30 to 40 km, under topography that increases from 0 to 2, 600 m; and became shallower (16 km depth) as the profile reaches the Gulf of California. These results show that deeper Moho is related to higher elevations with an abrupt change under the Main Gulf Escarpment, except for western PRBC where the Moho depth is not simply reflecting isostatic compensation. Key Points: Moho variations in Northern Baja California Receiver functions of stations belonging to the Northwest Mexico seismic network Crustal thickness of the Peninsular Ranges of Baja California and the Mexicali Valley